Energy-Saving Techniques in the Next Generation of Mobile Communication Networks - Viroslava Kapustynska (Engineering Proceedings)
The generalized integration of new communication technologies is expected to improve the lives of humans and edge us closer to achieving the Sustainable Development Goals in the next ten years. People will benefit from the rapid exchange of information, high-speed data transfer, the high-quality protection of uploaded and transmitted information, greater accessibility to medicine, the development of smart cities and homes, etc. But there are factors that significantly hinder the spread of fifth-generation mobile networks, the most critical being the high energy consumption that comes with the rapidly growing number of devices, machines, and mobile subscribers. Most often, base stations always operate at full capacity, but there are statistics that show that the flow of base station clients is not always the same, so energy consumption may be managed. It was found that cell zooming algorithms that mostly consider client flow can save 14–80% of base station power consumption; however, not all studies pay attention to the quality of service. By balancing energy saving and the quality of service, base station energy savings of about 15% can be achieved. In modern research, dynamic network scaling algorithms are more often presented, and location management investigation has been identified as a solution that can help improve energy-saving techniques and keep the quality of service at the optimal level.